The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2014
DOI: 10.4103/0974-2700.136862
|View full text |Cite
|
Sign up to set email alerts
|

Procedural sedation for pediatric patients in the emergency department at King Khalid University Hospital, Riyadh, K.S.A

Abstract: Procedural sedation and analgesia (PSA) has become the standard of care for diagnostic and therapeutic procedures undertaken in the Emergency Department (ED). In the Pediatric Emergency Department (PED) of King Khalid University Hospital (KKUH), which is a major teaching hospital in Riyadh Kingdom of Saudi Arabia we developed a standard protocol for PSA since 2005. The aim of this article is to report the experience at KKUH in pediatric PSA. Objectives: To report the experience at KKUH in pediatric PSAObjectiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 20 publications
0
4
0
Order By: Relevance
“…Ketamine is an analgesic that has been shown to help to decrease acute pain in the ED . With the morbidity and mortality associated with the ongoing opioid epidemic, there is an urgent need to find nonopioid alternatives to treat pain that are safe and effective . Our study demonstrated efficacy for SDDK at 0.5 and 0.25 mg/kg infused over 20 minutes to reduce pain in our population of chronic pain patients during their ED stay.…”
Section: Discussionmentioning
confidence: 74%
“…Ketamine is an analgesic that has been shown to help to decrease acute pain in the ED . With the morbidity and mortality associated with the ongoing opioid epidemic, there is an urgent need to find nonopioid alternatives to treat pain that are safe and effective . Our study demonstrated efficacy for SDDK at 0.5 and 0.25 mg/kg infused over 20 minutes to reduce pain in our population of chronic pain patients during their ED stay.…”
Section: Discussionmentioning
confidence: 74%
“…According to the results presented in that study, adverse events were witnessed in 10 patients, of which six out of the nine patients that received ketamine for procedural sedation vomited [22].…”
Section: Discussionmentioning
confidence: 98%
“…Similarly, a previous study that commonly used ketamine for procedural sedation reported that vomiting and nausea were the most common adverse events observed in the patients. According to the results presented in that study, adverse events were witnessed in 10 patients, of which six out of the nine patients that received ketamine for procedural sedation vomited [ 22 ].…”
Section: Reviewmentioning
confidence: 99%
“…Ozkan et al22 reported 12.1% nausea and 7.9% vomiting during their practice of elective surgery in the pediatric population. Salleeh et al23 used ketamine in 179 pediatric emergency patients for painful and traumatic, diagnostic and therapeutic procedures and reported 60% of vomiting to be the most frequently observed side effect. In our study 30 patients in Group 1 (3.3%) had nausea in line with literature, but we did not come across vomiting.…”
Section: Discussionmentioning
confidence: 99%